Cote d'Ivoire : First Reviews Under Extended Arrangement Under the Extended Fund Facility and an Arrangement Under the Extended Credit Facility, and Requests for Modification of Performance Criteria and Augmentation of Access-Press Release; Staff Report; and Statement by the Executive Director for Cote d'Ivoire. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Cote d'Ivoire's First Reviews under Extended Arrangement under the Extended Fund Facility (EFF), an Arrangement under the Extended Credit Facility (ECF), and the Request for Modification of Performance Criteria (PCs) and Augmentation of Access. Growth is projected at about 7 percent a year in 2017-19, and inflation is expected to remain subdued. Falling world cocoa prices and rising oil prices are cutting into export receipts and fiscal revenues. The IMF staff supports the authorities' requests for augmentation of program access under the ECF and EFF arrangements and modification of end-June 2017 PCs.